Darnton, Robert, Editing and Subversion. Clandestine literature in the old regime. Mexico: Turner & Fce, 2003 - Bonilla, Javier (InMediaciones de la Comunicación, 2016)
For those who do not know the intellectual journey of Robert Darnton, suffice it to say that he is one of the most recognized specialists in cultural history of the eighteenth century in France. As if this were not enough, he has specialized, simultaneously, in a sort of historical sub-discipline, something like "a history of publishing and the book", of which he is a pioneer and in which he has established himself as the most known specialist. In this book Darnton reaffirms some of the features of the immense eighteenth-century clandestine literature and discusses and analyzes the enormous quantities of literature prohibited in France at the end of the Old Regime. (Complete article in spanish language).